Epimeria (Pseudepimeria) debroyeri d'Acoz & Verheye 2017 - d'Acoz, Cédric d'Udekem; Verheye, Marie L. (Zenodo, 2017)
Epimeria ( Pseudepimeria ) cf. debroyeri Fig 272 Material examined RV Polarstern cruises: SOUTHERN OCEAN: 1 juv., cruise PS69, ANT-XXIII/8, stn 614-3/4/5, Elephant Island, 60°52.37ʹ S, 55°29.80ʹ W to 60°52.71ʹ S, 55°27.83ʹ W, 248–265 m, a lot of epifauna, Rauschert dredge and Agassiz trawl, 22 Dec. 2006, coll. C. d’Udekem d’Acoz and H. Robert (RBINS, INV. 132941); 1 white juv., photographed, cruise PS69, ANT-XXIII/8, stn 728-2, south of Dundee Island, 63°42.63ʹ S, 56°01.63ʹ W to 63°42.25ʹ S, 56°02.16ʹ W, 293–298 m, Agassiz trawl, 24 Jan. 2007, coll. C. d’Udekem d’Acoz and H. Robert (RBINS, INV. 122524). Colour pattern Body and appendages entirely white; eyes reddish. Remarks These two specimens possibly belong to Epimeria debroyeri sp. nov. However, they are much smaller (8 mm instead of 33 mm) and exhibit a number of differences, especially in the development of their mid-dorsal crests. It has to be noted that these differences might be size-related. The two specimens are therefore referred as E. cf. debroyeri . : Published as part of d'Acoz, Cédric d'Udekem & Verheye, Marie L., 2017, Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea), pp. 1-553 in European Journal of Taxonomy 359 on page 129, DOI: 10.5852/ejt.2017.359, http://zenodo.org/record/3855694